Investigation of Equating Error in Tests with Differential Item Functioning - Meltem Yurtçu; Cem Oktay Güzeller (International Journal of Assessment Tools in Education)
In this study purposes to indicate the effect ofthe number of DIF items and the distribution of DIF items in these forms, whichbe equalized on equating error. Mean-mean, mean-standard deviation, Haebara andStocking-Lord Methods used in common item design equal groups as equalizationmethods. The study included six different simulation conditions. The conditionswere compared according to the number of DIF items and the distribution of DIFitems on tests. The results illustrated that adding DIF items to tests wereequated caused an increase in the errors obtained by equating methods. We maystate that the change in errors is lowest in characteristic curvetransformation methods, largest in moment methods depending on the situationsin these conditions.